Research on Civil Aviation Safety Supervision Capability Evaluation Model Based on Entropy Weight TOPSIS - Weichun Li (Forest Chemicals Review)
Taking the safety concept proposed by ICAO and the classical SHEL model in the field of aviation safety as the theoretical basis, in combination with the characteristics of civil aviation safety supervision, the evaluation index system of civil aviation safety supervision capability is constructed from the perspective of finding the safety problems of administrative counterparts in civil aviation safety supervision, including 12 evaluation indicators in 4 dimensions: "issues of institutional responsibilities", "issues related to people", "issues related to equipment and facilities environment" and "issues related to system procedures". The entropy weight method was used to calculate the weight of each evaluation index, and then the TOPSIS method was used to comprehensively rank the safety supervision capability of the civil aviation regional administrations. The study shows that the entropy TOPSIS method, as a mathematical modeling method based on data itself, can reduce the subjectivity of experts’ assignments and can provide a scientific basis for the evaluation of civil aviation safety supervision capability.